Vapor-phase of essential oils as a promising solution to prevent Candida vaginal biofilms caused by antifungal resistant strains - Fernandes, Liliana Sousa (2022)
Background: Vulvovaginal candidiasis (VVC) is a disease with high incidence, a huge impact on the quality of life and health of women, and which represents a great challenge to treat. The growing need to apply antifungal intensive therapies have contributed to an emergence of drug-resistant Candida strains. Thus, effective therapeutic options, to meet the antifungal-resistance challenge and to control high resilient biofilms, are urgently needed. This study aimed to investigate the antifungal activity of essentials oils (EOs) on drug-resistant Candida vaginal isolates. Method: Therefore, the antimicrobial effect of tea tree, niaouli, white thyme, and cajeput EOs on the planktonic growth of Candida isolates was initially evaluated by an agar disc diffusion method. Then, the vapor-phase effect of tea tree EO (VP-TTEO) on biofilm formation and on pre-formed biofilms was evaluated by crystal violet staining, XTT reduction assay, colony forming units’ enumeration, and scanning electron microscopy. Results: The results revealed high antifungal activity of EOs against drug-resistant Candida isolates. Additionally, the VP-TTEO showed a significant inhibitory effect on the biofilm formation of all tested isolates and was able to provoke an expressive reduction in mature Candida albicans biofilms. Conclusions: Overall, this study suggests that the VP-EO may be a promising solution that is able to prevent biofilm-related VVC caused by antifungal-resistant strains.